Comparison of quality of UTC(PL) and UTC(NPL) scales prediction by means of GMDH Neural Network = Porównanie jakości prognozowania skal UTC(PL) i UTC(NPL) z zastosowaniem sieci neuronowej GMDH - Sobolewski, Łukasz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents research results on predicting the deviations for two different timescales, UTC(PL) and UTC(NPL) by means of GMDH type Neural Network. UTC(PL) timescale was realized by commercial caesium atomic clock. The UTC(NPL) timescale, on the other hand, is based on an active hydrogen maser, additionally supervised by the primary frequency standard in the form of a caesium fountain.
Keywords: jakość prognozowania; UTC(PL); UTC(NPL); sieci neuronowe